Mitochondria Dysfunction and Cell Apoptosis Limit Resistance of Nile Tilapia (Oreochromis niloticus) to Lethal Cold Stress - Ran Liu; Renyan Liu; Guili Song; Qing Li; Zongbin Cui; Yong Long (Animals, 2022)
Inability of Nile tilapia (Oreochromis niloticus) to withstand cold stress represents a major economic concern, which restricts the culture area, limits the growing period and even results in mass mortality in cold seasons. However, the cellular and molecular mechanisms determining cold susceptibility of Nile tilapia remain largely unknown. In this study, we characterized the ability of juvenile Nile tilapia to survive lethal cold stress (12 °C) and the median survival time (LT50) of the experimental fish under exposure to 12 °C cold stress was estimated as 3.14 d. After being exposed to 12 °C for 3 d, the survivors that lost equilibrium (LE) and those that swam normally (NO) were regarded as cold-sensitive and cold-tolerant, respectively. The untreated (Ctrl), NO and LE fish were subjected to histological, biochemical and gene expression analyses to explore the cellular and molecular events underlying cold susceptibility of Nile tilapia. Exposure of Nile tilapia to lethal cold stress caused systemic tissue structure changes, mitochondrial swelling and dysfunction, induction of apoptosis and endoplasmic reticulum (ER) stress-related genes and cell apoptosis. The extent of these adverse cellular and molecular events determines an individual’s ability to survive cold stress. Our data indicate that mitochondria dysfunction and mitochondria-mediated cell apoptosis are the main factors limiting Nile tilapia’s cold resistance.